A high-corrosion-resistant and high-toughness economical steel and its preparation method
By accurately controlling the content of Cr, Ni, Mn, Mo, N elements and heat treatment process in corrosion-resistant steel, a mixed structure of ferrite + austenite + martensite is obtained, which solves the problems of low toughness and high cost of existing corrosion-resistant steels, and realizes the preparation of high corrosion-resistant and high toughness economical steels.
Patent Information
- Application Number
- CN202211606627.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The existing corrosion-resistant steel alloys have high element content, low toughness and high cost, making it difficult to meet the needs of large-scale production and practical applications.
By precisely controlling the mass percentage of Cr, Ni, Mn, Mo, and N elements in the steel, combined with the solid solution heat treatment process after thermal deformation, a mixed structure of ferrite + austenite + martensite is obtained to improve the corrosion resistance and toughness of the steel.
The preparation of high corrosion resistance and high toughness economical steel is achieved, which reduces the cost of raw materials and improves the comprehensive performance of the material, including high strength, good corrosion resistance and welding performance.
Smart Images

Figure CN116121664B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corrosion-resistant steel, and in particular to a highly corrosion-resistant and high-toughness economical steel and a preparation method thereof. Background Art
[0002] Oil well pipe is an important consumable in the process of oil and gas exploration and development, accounting for about 40% of the total steel used in the oil and gas industry, and is an important part of oil and gas extraction equipment. As an important petroleum equipment material, oil well pipe accounts for an average of 20% to 30% of the entire well construction cost. Therefore, whether the entire petroleum project can proceed smoothly is inseparable from the quality of oil well pipe. The oil well pipe is placed in the casing and used to collect oil and gas. Due to the flow of corrosive liquids in the oil well pipe, various corrosion-resistant products must be selected according to the corrosion conditions. At present, the material for oil well pipes that resist CO2 corrosion is mainly 13Cr martensitic stainless steel, but martensitic steel cannot be used in an environment containing H2S. Although the use of 22Cr (or 25Cr, 27Cr, the higher the Cr content, the better the corrosion resistance) duplex stainless steel with a higher alloy content can meet the use requirements of oil well pipes, the material cost is high and is not suitable for large-scale industrial applications in oil and gas extraction scenarios.
[0003] In view of the above-mentioned material selection problem, economical duplex stainless steel (such as 2101, 2304, etc.) with Mn and N instead of Ni as austenite stabilizing elements has become one of the options that take into account both low cost and high performance of raw materials. However, higher Mn and N content increases material casting defects, deteriorates hot working properties, and thus reduces the material yield rate. On the other hand, it increases the maximum precipitation temperature of the precipitated phase and narrows the hot working temperature range, which is not conducive to industrial production. The low yield rate causes the actual production cost of the product to remain high, and the narrow hot working window makes material processing and production difficult. In addition, in actual industrial production, the corrosion resistance of stainless steel is usually measured by PREN (pitting resistance equivalent) value. The addition of Mn element will reduce the stainless steel PREN value, that is, reduce its corrosion resistance. Existing economical stainless steel usually adds a higher Mn element (≥5), and its corrosion resistance must be adversely affected. The above reasons together lead to the fact that although economical duplex stainless steel has good mechanical properties at a lower raw material cost, it is still difficult to produce and apply on a large scale.
[0004] At present, there are many patents for stainless steel varieties and corresponding process flows in this field, but most of them have problems such as high costs or complex processes and cannot meet the needs of mass production and practical applications. Summary of the invention
[0005] In view of the above situation, the present invention aims to provide a highly corrosion-resistant and high-toughness economical steel and a preparation method thereof, so as to solve the problems of high alloy element content, low toughness and high cost of existing corrosion-resistant steel.
[0006] The purpose of the present invention is mainly achieved through the following technical solutions:
[0007] On the one hand, the present invention provides a highly corrosion-resistant and high-toughness economical steel. The components of the highly corrosion-resistant and high-toughness economical steel include, by mass percentage: C: ≤0.03%, Cr: 18.0%~20.0%, Mo: 0.5%~3.0%, Ni: 1.0%~2.8%, Mn: 1.0%~4%, Si: 0.1%~0.5%, N: 0.1%~0.25%, P: ≤0.03%, S: ≤0.01%, and the balance is Fe and unavoidable impurities.
[0008] Furthermore, in the composition of high corrosion resistant and high toughness economical steel, Cr+3.3Mo+30N-Mn≥26.
[0009] Furthermore, in the composition of high corrosion-resistant and high-toughness economical steel, 30Ni+17Mn-12Mo-800N≤0.
[0010] Furthermore, the components of the high corrosion-resistant and high-toughness economical steel include, by mass percentage: C: 0.02%~0.03%, Cr: 18.5%~19.5%, Mo: 1.0%~2.5%, Ni: 1.0%~1.5%, Mn: 1.5%~2.8%, Si: 0.3%~0.5%, N: 0.15%~0.25%, P: ≤0.03%, S: ≤0.01%, and the balance is Fe and unavoidable impurities.
[0011] Furthermore, in the composition of high corrosion resistant and high toughness economical steel, Cr+3.3Mo+30N-Mn≥28.
[0012] Furthermore, the microstructure of the highly corrosion-resistant and high-toughness economical steel is a mixed structure of ferrite + austenite + martensite.
[0013] Furthermore, in the microstructure of the high corrosion resistance and high toughness economical steel, the volume percentage of austenite is 30% to 50%, and the volume percentage of martensite is 5% to 15%.
[0014] On the other hand, the present invention also provides a method for preparing a highly corrosion-resistant and high-toughness economical steel, which is used to prepare the highly corrosion-resistant and high-toughness economical steel, comprising:
[0015] Step 1: Melting metal raw materials into molten steel;
[0016] Step 2: smelting the molten steel into continuous casting billets or ingots by continuous casting or mold casting;
[0017] Step 3: heating and keeping the continuous casting billet or ingot warm, forging and opening the billet to form a forging billet;
[0018] Step 4: hot rolling the forged billet into a plate through multiple passes;
[0019] Step 5: subject the hot-rolled plate to solid solution treatment to obtain highly corrosion-resistant and high-toughness economical steel.
[0020] Furthermore, in step 3, the forging temperature is 1150-1250°C.
[0021] Furthermore, in step 5, the temperature of the solution treatment is 1000-1150°C.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] a) The high corrosion resistant and high toughness economical steel of the present invention accurately controls the mass percentage of Cr, Ni, Mn, Mo, and N elements in the steel, and combined with the solution heat treatment process after hot deformation, it can obtain a mixed structure of ferrite + austenite + martensite, which greatly improves the corrosion resistance and toughness of the steel. Since the three-phase stainless steel material of the present invention has an ultrafine martensite phase, the tensile strength of the material is better than that of the duplex stainless steel with a higher Cr content, and high strength is achieved with a lower Cr content. Compared with the martensitic stainless steel in the prior art, the ferrite phase and the austenite phase are introduced into the stainless steel of the present invention to obtain better intergranular corrosion resistance and H2S stress corrosion resistance. The content of austenite phase in the three-phase stainless steel of the present invention is much higher than that of martensitic stainless steel. It is difficult for martensitic stainless steel to obtain an austenite phase with a volume content greater than 20% while maintaining strength. Therefore, the three-phase stainless steel material of the present invention has better resistance to H2S stress corrosion.
[0024] b) Traditional precipitation strengthening and precipitation hardening are mainly based on intermetallic compounds and precipitated phases, which can improve strength, but cause a significant decrease in the corrosion resistance of the material. The steel of the present invention uses fine martensitic particles as the third phase for strengthening, and by regulating the stability of austenite, dispersed fine martensitic particles are precipitated in the austenite. These martensitic particles are distributed in the austenite phase in two forms: first, they are evenly dispersed in the austenite grains as fine particles, and the other is distributed in the austenite grains in discontinuous, irregular granular form. As a strengthening phase, the martensitic phase has the same composition as the matrix. Compared with intermetallic compounds, it is not easy to become the initiation point of pitting corrosion, and it is even less likely to become a cracking source of plastic deformation. Therefore, the steel of the present invention has excellent plasticity while having high strength and excellent corrosion resistance.
[0025] c) The high corrosion-resistant and high-toughness economical steel of the present invention is a three-phase structure. The steel of the present invention has the characteristics of low Cr and low alloy element content to obtain higher strength. It can also have the characteristics of high strength, resistance to intergranular corrosion, stress corrosion, high toughness and good welding performance, and has excellent comprehensive performance. At the same time, the composite structure of martensite and austenite can increase the interface density in the organization, thereby obtaining high-strength mechanical properties that are superior to traditional duplex stainless steel. Its balanced phase ratio in the conventional hot working temperature range (900-1180°C) brings excellent hot working performance. The multi-phase composite organizational form after solution treatment has better corrosion resistance than single-phase martensitic stainless steel while ensuring certain cold working performance.
[0026] d) The steel of the present invention not only ensures high strength, good plasticity and toughness, and excellent corrosion resistance, but also ensures that the yield strength of the steel of the present invention is greater than 480MPa (e.g. 481-510MPa), the tensile strength is greater than 800MPa (e.g. 806-850MPa), and the elongation is greater than 45% (e.g. 46.0%-56%). (180℃) CO2 corrosion rate 0.021g / m 2 h or less (e.g. 0.0167 to 0.0205 g / m 2 h); (200℃) CO2 corrosion rate 0.08g / m 2 h or less (e.g. 0.045 to 0.076 g / m 2 h); pitting corrosion rate 2.1g / m 2 h or less (e.g. 1.7 to 2.093 g / m 2 h); crevice corrosion rate 5.5g / m 2 h or less (e.g. 3.5 to 5.453 g / m 2 h); H2S stress corrosion test was passed.
[0027] e) The steel of the present invention has good toughness and excellent corrosion resistance, and has both the high strength of super martensitic stainless steel oil well pipe materials and the stress corrosion resistance, intergranular corrosion resistance and resistance to a small amount of H2S stress corrosion of duplex stainless steel. Since the Cr and Ni content of the steel of the present invention is low, the raw material cost is equivalent to or even slightly lower than that of the super 13Cr martensitic stainless steel in the prior art, and the hot working performance is good, so the steel of the present invention has low comprehensive cost, is economical and practical.
[0028] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the written description, claims, and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0030] Figure 1 The microstructure diagram of the steel after solution treatment according to Example 1 of the present invention;
[0031] Figure 2 This is an EBSD image of the steel of Example 1 of the present invention;
[0032] Figure 3 The microstructure diagram of the steel of Example 2 of the present invention;
[0033] Figure 4 The microstructure diagram of the steel of Example 3 of the present invention;
[0034] Figure 5 The microstructure diagram of the steel of Example 4 of the present invention;
[0035] Figure 6 One of the martensite morphologies in the steel of Example 1 of the present invention;
[0036] Figure 7 This is the second martensite morphology in the steel of Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used to illustrate the principles of the present invention together with the embodiments of the present invention.
[0038] The present invention provides a high-corrosion-resistant and high-toughness economical steel, wherein the components of the high-corrosion-resistant and high-toughness economical steel include, by mass percentage, C: ≤0.03%, Cr: 18.0%-20.0%, Mo: 0.5%-3.0%, Ni: 1.0%-2.8%, Mn: 1.0%-4%, Si: 0.1%-0.5%, N: 0.1%-0.25%, P: ≤0.03%, S: ≤0.01%, and the remainder is Fe and unavoidable impurities. Among them, Cr+3.3Mo+30N-Mn≥26, and 30Ni+17Mn-12Mo-800N≤0; wherein Cr, Mo, N, Ni, and Mn refer to the mass percentage of these elements × 100. For example, the mass percentage of the Cr element is 18.4%, and the Cr here is 18.4.
[0039] The following is a detailed description of the effects and dosage of the components in the present invention:
[0040] C: Although the addition of carbon can significantly improve the hardness and strength of steel, due to the high diffusion capacity of carbon, it is easy to combine with Cr to form M 23C6 type carbide, this type of carbide is mainly precipitated quickly (≤0.5 hours) in the temperature range of 700-900°C, or precipitated when kept at 550-700°C for a long time. The precipitation of carbides causes local Cr deficiency, increases the intergranular corrosion sensitivity of the material, and deteriorates the corrosion resistance. Therefore, in the present invention, the comprehensive effect of strength and corrosion resistance is comprehensively considered, and its content is controlled to be ≤0.03%.
[0041] Cr: The main element to ensure the corrosion resistance of stainless steel. It is also a ferrite-forming element. Improper control of Cr content will increase the ferrite content in the organization and reduce the strength. Considering comprehensive considerations, its content should be controlled at 18.0% to 20.0%.
[0042] Ni: It is an element that strongly forms and stabilizes austenite and expands the austenite phase region. Ni is an element that improves the toughness of stainless steel and the corrosion resistance of reducing media. Ni is also an important element for improving the resistance of austenite phase to transgranular stress corrosion in various media. At the same time, compared with Mn element, Ni element can reduce the cold working hardening tendency of austenite phase. Considering cost control, the present invention controls its content within 1.0% to 2.8%.
[0043] Mn: It can improve the solubility of N in steel and inhibit the precipitation of harmful phase chromium nitride, but Mn reduces the toughness of stainless steel. Compared with Ni, Mn is an economical austenite-forming element. Mn has different hardening effects on the austenite phase of stainless steel and the overall material. Too high Mn content will reduce the corrosion resistance of the material. Therefore, the present invention controls its content within 1.0% to 4%.
[0044] Mo: In addition to improving the corrosion resistance of stainless steel in oxidizing media, it also has a good effect on improving the corrosion resistance of stainless steel in reducing media. At the same time, in order to ensure pitting resistance, alloy elements such as Cr and Mo that increase the PREN value should not be too low. At the same time, alloy cost control and phase balance must also be considered. Comprehensively considered, its content is controlled to 0.5% to 3.0%.
[0045] Si: Si is added as a deoxidizer during the smelting process to achieve a deoxidation effect. Too much addition will deteriorate the intergranular corrosion resistance of the material. The present invention controls its content to 0.1% to 0.5%.
[0046] N: Like Ni, it is an element that strongly forms and stabilizes austenite and expands the austenite phase. N can also significantly improve the pitting corrosion resistance of the austenite phase in stainless steel, thereby improving the overall pitting corrosion resistance of stainless steel. In some media, N has a good effect on the stress resistance of stainless steel, and there is an optimal value. Further increasing the N content will reduce its stress corrosion resistance. N is also a relatively economical alloying element, but N reduces the hot working performance of stainless steel. Therefore, the present invention controls its content to 0.1% to 0.25%.
[0047] S: It will significantly reduce the hot working performance of steel and easily react with Mn to form MnS inclusions, which will reduce the material's resistance to pitting corrosion and crevice corrosion. Therefore, its content is controlled to ≤ 0.01%.
[0048] P: It is a harmful impurity element that will not only deteriorate the plasticity of the material, but also reduce the corrosion resistance of the material. Therefore, its content is controlled to be ≤0.03%.
[0049] Specifically, the present application comprehensively considers three aspects: guarantee of corrosion resistance, raw material cost caused by alloy element matching, precipitation of harmful phases caused by alloy element matching, and cost change caused by hot working yield. In addition to controlling the content of individual elements of the main alloying elements Cr, Ni, Mn, and N in steel, in order to ensure corrosion resistance, Cr+3.3Mo+30N-Mn≥26 is controlled. In order to make the maximum precipitation temperature of harmful phases lower than 750°C and ensure that the material has good hot working properties, and considering that the three-phase ratio can be controllable during hot working between 900 and 1180°C, it is necessary to control the content of Ni, Mn, Mo, and N elements to meet the following requirements: 30Ni+17Mn-12Mo-800N≤0.
[0050] In order to further improve the comprehensive performance of the above-mentioned high corrosion resistant and high toughness economical steel, the components of the above-mentioned high corrosion resistant and high toughness economical steel can be calculated by mass percentage: C: 0.02%~0.03%, Cr: 18.5%~19.5%, Mo: 1.0%~2.5%, Ni: 1.0%~1.5%, Mn: 1.5%~2.8%, Si: 0.3%~0.5%, N: 0.15%~0.25%, P: ≤0.03%, S: ≤0.01%, and the balance is Fe and unavoidable impurities.
[0051] Specifically, Cr+3.3Mo+30N-Mn≥28.
[0052] Specifically, 30Ni+17Mn-12Mo-800N≤-80.
[0053] The present invention also provides a method for preparing the above-mentioned high corrosion resistance and high toughness economical steel, comprising:
[0054] Step 1: Melting metal raw materials into molten steel;
[0055] Step 2: smelting the molten steel into continuous casting billets or ingots by continuous casting or mold casting;
[0056] Step 3: heating the continuous casting billet or ingot to 1150-1250° C. and keeping the temperature for 1-3 hours, then forging and opening the billet to form a forging billet;
[0057] Step 4: After heating the forging billet to 1150-1250°C and keeping it at this temperature for 1-3 hours, hot rolling it into a plate through multiple passes;
[0058] Step 5: subjecting the hot-rolled plate to a solution treatment at 1000-1150°C for 1-2 hours to obtain a highly corrosion-resistant and highly tough economical steel. The highly corrosion-resistant and highly tough economical steel has a three-phase structure of 5%-15% martensite, 30%-50% austenite, and the rest ferrite.
[0059] Specifically, in the above steps 1 and 2, a converter or electric furnace is used for smelting, LF refining and casting into ingots.
[0060] Specifically, in the above step 3, the forging temperature is 1150-1250°C. This is because the material of the present invention is a two-phase ferrite + austenite at a temperature higher than 800°C. The ratio of the two phases changes with the heating temperature. The higher the heating temperature, the more ferrite content, and the corresponding austenite content decreases. Selecting this temperature range for heating ensures the full dissolution of harmful precipitated phases, and also makes the ferrite phase content in the material greater than 70%, so that the steel is forged in a single-phase region with better thermoplasticity, avoiding the difference in the thermal deformation capacity of the two phases of ferrite and austenite, which leads to the uncoordinated deformation of the two phases in the forging process and causes forging cracking.
[0061] Specifically, in the above step 4, the hot-rolled sheet is water-cooled to room temperature to avoid the precipitation of harmful phases.
[0062] Specifically, in the above step 5, it is necessary to adjust the two-phase ratio, austenite stability and martensite content through a reasonable solution heat treatment temperature. The solution temperature is not lower than 950°C to prevent harmful phase precipitation and excessive martensite content, and the solution temperature is not higher than 1150°C to avoid too low austenite content, which reduces toughness and corrosion resistance. Therefore, the hot-rolled plate is solution treated at 1000-1150°C for 1-2 hours.
[0063] Specifically, the microstructure of the above-mentioned high corrosion resistance and high toughness economical steel is a mixed structure of ferrite + austenite + martensite, wherein the volume percentage of austenite is 30% to 50%, and the volume percentage of martensite is 5% to 15%.
[0064] Specifically, in the microstructure of the above-mentioned high corrosion resistance and high toughness economical steel, martensite particles exist in the austenite phase in two forms: one is fine particles uniformly dispersed in the austenite grains (such as Figure 6 The other is distributed in the austenite grains in a discontinuous and irregular granular form (as shown in Figure 7 As shown in Figure 2, almost all martensite particles are covered by austenite. The thickness of the martensite sheet is less than 90nm.
[0065] The present invention controls the stability of austenite to a critical state through reasonable composition design, and controls a trace amount of austenite to undergo quenching martensite phase transformation through a specific solid solution temperature, and precipitates dispersed fine martensite particles in the austenite. These martensite particles exist in the austenite phase in two forms. First, they are evenly dispersed in the austenite grains (such as Figure 6 The other is distributed in the austenite grains in a discontinuous and irregular granular form (as shown in Figure 7 As shown), and almost all martensite particles are coated with austenite. On the one hand, a small amount of quenched martensite can promote the occurrence of austenite deformation-induced martensitic phase transformation, providing conditions for the continuous and uniform phase transformation-induced plasticity of austenite; on the other hand, quenched martensite, as the third phase formed during the heat treatment process, has a strength and hardness far higher than that of ferrite and austenite. It is dispersed in austenite with fine particles, dividing austenite grains, and has the effect of refining the austenite grain size. At the same time, it acts as a hard phase to pin dislocations and play a role in composite strengthening. The precipitation of quenched martensite particles also changes the phase morphology of austenite, increases the interface density in the organization, and increases the strength of the material. In addition, quenched martensite, as a strengthening phase, has the same composition as the matrix. Compared with intermetallic compounds, it is not easy to become a pitting initiation source, and it is even less likely to become a cracking source of plastic deformation. Therefore, the steel of the present invention has excellent plasticity while having high strength and excellent corrosion resistance.
[0066] Compared with the prior art, the high corrosion resistant and high toughness economical steel of the present invention accurately controls the mass percentage of Cr, Ni, Mn, Mo, and N elements in the steel, and combined with appropriate heat treatment processes, a mixed structure of ferrite + austenite + martensite can be obtained, which greatly improves the corrosion resistance and toughness of the steel. In stainless steel, the increase in Cr content can improve the strength of the material, but because the three-phase stainless steel material of the present invention has ultrafine martensite, the tensile strength of the material is better than that of duplex stainless steel with a higher Cr content. Compared with the duplex stainless steel of the prior art, the three-phase structure stainless steel of the present invention controls the content combination of Cr, Ni, Mn, Mo, and N, and obtains a three-phase structure with adjustable martensite content after hot rolling. Through a reasonable heat treatment process, high toughness mechanical properties and high corrosion resistance are achieved with a lower Cr content. Compared with the martensitic stainless steel of the prior art, the stainless steel of the present invention introduces ferrite and austenite to obtain better intergranular corrosion resistance and H2S stress corrosion resistance. The austenite content in the stainless steel of the present invention is much higher than that in martensitic stainless steel. It is difficult to obtain an austenite content greater than 20% in martensitic stainless steel. Therefore, the steel of the present invention has better hydrogen embrittlement resistance.
[0067] The high corrosion-resistant and high-toughness economical steel of the present invention is a three-phase structure. The steel of the present invention has the characteristics of low Cr and low alloy element content to obtain higher strength. It can simultaneously have the characteristics of high strength, resistance to intergranular corrosion, stress corrosion, high toughness and good welding performance, and has excellent comprehensive performance. At the same time, the composite structure of martensite and austenite can increase the interface density in the organization, thereby obtaining high-strength mechanical properties that are superior to traditional duplex stainless steel. Its balanced phase ratio in the conventional hot working temperature range (900-1180°C) brings excellent hot working performance. The multi-phase composite organizational form after solution treatment has better corrosion resistance than single-phase martensitic stainless steel while ensuring certain cold working performance.
[0068] The steel of the present invention not only ensures high strength, good plasticity and toughness, and excellent corrosion resistance, but also ensures that the yield strength of the steel of the present invention is greater than 480MPa (e.g. 481-510MPa), the tensile strength is greater than 800MPa (e.g. 806-850MPa), and the elongation is greater than 45% (e.g. 46.0%-56%). (180°C) CO2 corrosion rate 0.021g / m 2 h or less (e.g. 0.0167 to 0.0205 g / m 2 h); (200℃) CO2 corrosion rate 0.08g / m 2 h or less (e.g. 0.045 to 0.076 g / m 2 h); pitting corrosion rate 2.1g / m 2 h or less (e.g. 1.7 to 2.093 g / m 2 h); crevice corrosion rate 5.5g / m 2 h or less (e.g. 3.5 to 5.453 g / m 2 h); H2S stress corrosion test was passed.
[0069] The steel of the present invention has good toughness and excellent corrosion resistance, and has both the high strength of super martensitic stainless steel oil well pipe materials and the stress corrosion resistance, intergranular corrosion resistance and small amount of H2S stress corrosion resistance of duplex stainless steel. Since the Cr and Ni content of the steel of the present invention is low, the raw material cost is equivalent to or even slightly lower than that of the super 13Cr martensitic stainless steel in the prior art, and the hot working performance is good, so the steel of the present invention has low comprehensive cost, is economical and practical.
[0070] Examples 1-4
[0071] The advantages of precise control of the composition and process parameters of the steel of the present invention are demonstrated below with specific examples and comparative examples. 13Cr is selected as a comparison object for corrosion performance.
[0072] Examples 1-4 of the present invention provide a highly corrosion-resistant and high-toughness economical steel and a preparation method thereof. The chemical compositions of the steels of Examples 1-4 are shown in Table 1.
[0073] The preparation method of Example 1 comprises:
[0074] Step 1: Melting metal raw materials into molten steel; using a die casting method to smelt the molten steel into steel ingots to obtain ingots;
[0075] Step 2: After heating the ingot to 1150°C and keeping the temperature for 2 hours, forging and opening the ingot to form a forging ingot;
[0076] Step 3: Keep the forging billet at 1200°C for 2 hours and hot-roll it into a plate in multiple passes;
[0077] Step 4: The hot-rolled plate is solution treated for 1 hour, and the three-phase structure content is adjusted by controlling the solution treatment temperature to 1050°C, with a ferrite content of 50%, a martensite content of 8%, and an austenite content of 42%.
[0078] The preparation method of Example 2 comprises:
[0079] Step 1: Melting metal raw materials into molten steel; using a die casting method to smelt the molten steel into steel ingots to obtain ingots;
[0080] Step 2: After heating the ingot to 1180°C and keeping the temperature for 2 hours, forging and opening the ingot to make a forging ingot;
[0081] Step 3: Keep the forging billet at 1210°C for 2 hours and hot-roll it into a plate in multiple passes;
[0082] Step 4: The hot-rolled plate is solution treated for 1 hour, and the three-phase structure content is adjusted by controlling the solution treatment temperature to 1100°C, with a ferrite content of 52%, a martensite content of 6%, and an austenite content of 42%.
[0083] The preparation method of Example 3 comprises:
[0084] Step 1: Melting metal raw materials into molten steel; using a die casting method to smelt the molten steel into steel ingots to obtain ingots;
[0085] Step 2: After heating the ingot to 1200°C and keeping the temperature for 2 hours, forging and opening the ingot to make a forging ingot;
[0086] Step 3: Keep the forging billet at 1200°C for 2 hours and hot-roll it into a plate in multiple passes;
[0087] Step 4: The hot-rolled plate is subjected to solution treatment for 1 hour, and the three-phase structure content is adjusted by controlling the solution treatment temperature to 1100°C, with a ferrite content of 43%, a martensite content of 7%, and an austenite content of 50%.
[0088] The preparation method of Example 4 comprises:
[0089] Step 1: Melting metal raw materials into molten steel; using a die casting method to smelt the molten steel into steel ingots to obtain ingots;
[0090] Step 2: After heating the ingot to 1200°C and keeping the temperature for 2 hours, forging and opening the ingot to make a forging ingot;
[0091] Step 3: Keep the forging billet at 1200°C for 2 hours and hot-roll it into a plate in multiple passes;
[0092] Step 4: The hot-rolled plate is solution treated for 1 hour, and the three-phase structure content is adjusted by controlling the solution treatment temperature to 1000°C, with a ferrite content of 45%, a martensite content of 6%, and an austenite content of 49%.
[0093] The specific process parameters of Examples 1-4 are shown in Table 2, and the mechanical properties of Examples 1-4 are shown in Table 3. Figure 1 is a microstructure diagram of the steel of Example 1 of the present invention, Figure 2 This is an EBSD micrograph of the steel of Example 1 of the present invention, wherein the blue represents the FCC phase (austenite) and the red represents the BCC phase. It can be observed that a large number of fine conical martensite particles are precipitated inside the austenite.
[0094] Figure 3-Figure 5 The microstructures of the steels of Examples 2-4 of the present invention are shown in Table 4. The microstructure of the economical steel with high corrosion resistance and high toughness of the present invention is a mixed structure of ferrite + austenite + martensite, wherein the volume percentage of austenite is 30% to 50% (e.g., 40% to 50%), and the volume percentage of martensite is 5% to 15% (e.g., 6% to 13%), and martensite particles exist in the austenite phase in two forms: one is uniformly dispersed in the austenite grains as small particles, and the other is distributed in the austenite grains as discontinuous and irregular particles.
[0095] Table 1 Chemical composition wt%
[0096]
[0097] Table 2 Heat treatment process parameters of Examples 1-4
[0098] serial number Solution temperature, °C Example 1 1050 Example 2 1100 Example 3 1100 Example 4 1000
[0099] Table 3 Mechanical properties
[0100]
[0101] Table 4 Microstructure
[0102]
[0103]
[0104] In order to illustrate the corrosion resistance of the steel of the present invention, the corrosion resistance of the steel of Examples 1-4 was measured under 5 different conditions and compared with 13Cr under the same test conditions. This experiment was used to evaluate the corrosion resistance of the steel of the present invention in different corrosive environments. The results of the corrosion test are shown in Table 5, and the corresponding test conditions are as follows:
[0105] (180℃ or 200℃) The corrosion conditions of CO2 corrosion rate are as follows:
[0106] 1. Medium (formation water) mg / L: CO3 2- / 0,HCO3 - / 189,OH - / 0,Cl - / 128000,SO4 2- / 430,Ca 2+ / 8310,Mg 2+ / 561,K + / 6620,Na + / 76500);
[0107] 2. CO2 partial pressure: 4.48MPa, total test pressure: 10MPa;
[0108] 3. Test temperature: 180℃ or 200℃;
[0109] 4. Test time: 720 hours.
[0110] The corrosion conditions for pitting corrosion rate are as follows:
[0111] 1. Test temperature: 22±2℃;
[0112] 2. Medium: 100g reagent grade ferric chloride FeCl3·6H2O dissolved in 900mL IV reagent grade water (mass ratio about 6%);
[0113] 3. Test time: 72 hours;
[0114] 4. Sample size: 50×25×3mm, polished to 2000# sandpaper.
[0115] The corrosion conditions for crevice corrosion rate are as follows:
[0116] 1. The test temperature is 22±2℃;
[0117] 2. Dissolve 100g reagent grade ferric chloride FeCl3·6H2O in 900mL IV reagent grade water (mass ratio about 6%);
[0118] 3. Test time: 72 hours;
[0119] 4. Sample size: 50×25×3mm, polished to 2000# sandpaper.
[0120] The corrosion conditions of H2S stress corrosion test are as follows:
[0121] 1. The test temperature is 22±2℃;
[0122] 2. 50 g NaCl, 25 g [23.8 mL] CH3COOH, and 4.1 g CH3COONa were dissolved in 921 mL IV reagent grade water (about 5 wt% sodium chloride, 2.5 wt% glacial acetic acid, and 0.41 wt% sodium acetate by mass ratio);
[0123] 3. Test time: 720 hours;
[0124] 4. Sample size: 50×5×2mm, polished to 2000# sandpaper;
[0125] 5. Four-point bending test, loading force is 80% yield stress.
[0126] From Table 5, it can be seen that the (180°C) CO2 corrosion rate of the high corrosion resistant economical steel of Examples 1-4 is 0.021 g / m 2 h or less (e.g. 0.0167 to 0.0205 g / m 2 h); (200℃) CO2 corrosion rate 0.08g / m 2 h or less (e.g. 0.045 to 0.076 g / m 2 h); pitting corrosion rate 2.1g / m 2 h or less (e.g. 1.7 to 2.093 g / m 2 h); crevice corrosion rate 5.5g / m 2 h or less (e.g. 3.5 to 5.453 g / m 2 h); H2S stress corrosion test was passed. The corrosion resistance of Examples 1-4 of the present invention is better than that of 13Cr, especially the CO2 corrosion resistance at 200°C. The corrosion resistance of the present invention is much better than that of super 13Cr, and can be used in more harsh environments.
[0127] Table 5 Corrosion test data
[0128]
[0129]
[0130] The inventors have conducted a lot of in-depth research in the research. In order to further highlight the advantages of the present invention in terms of performance and composition, super 13Cr martensitic and high Mn economical duplex stainless steel are now listed as comparative examples as follows:
[0131] Comparative Example 1
[0132] The present comparative example provides a corrosion-resistant oil well pipe steel and a preparation method thereof. The corrosion-resistant oil well pipe steel of the present comparative example is 13Cr and is prepared by the current mature process of 13Cr. The composition of the corrosion-resistant oil well pipe steel of the present comparative example is C: 0.03%, Cr: 13%, Ni: 5%, Mo: 2%, Mn: 0.5%, Si: 0.5%, and the preparation method is as follows: after heating and forging at 1150°C, water cooling, reheating to 860°C for 2h, quenching, and tempering at 620°C for 1h.
[0133] The microstructure of the steel of this comparative example is martensite (93%) + austenite (7%). The mechanical properties are shown in Table 3 above, and the corrosion resistance results are shown in Table 5 above.
[0134] Comparative Example 2
[0135] This comparative example provides a corrosion-resistant steel tube and a preparation method thereof. The composition of the corrosion-resistant steel in this comparative example is shown in Table 1 above, and the preparation method is the same as that in Example 1.
[0136] The microstructure of the steel in this comparative example is ferrite (54%) + austenite (47%), the mechanical properties are as shown in Table 3 above, and the corrosion resistance results are as shown in Table 5 above.
[0137] It can be seen from the comparative examples that the high corrosion-resistant and high-toughness economical steel of the present invention accurately controls the mass percentages of Cr, Ni, Mn, Mo, and N elements in the steel, and combined with an appropriate heat treatment process, a mixed structure of ferrite + austenite + martensite can be obtained, which greatly improves the corrosion resistance and toughness of the steel. The cost of raw materials is equivalent to or even slightly lower than that of the super 13Cr martensitic stainless steel in the prior art. At the same time, the corrosion resistance is far better than that of 13Cr martensitic stainless steel. Compared with the high-Mn economical duplex stainless steel, the corrosion resistance and mechanical properties are more excellent. The steel of the present invention has low comprehensive cost, is economical, and is practical.
[0138] The steel of the present invention can be used in environments where strength, toughness and corrosion resistance of steel are required, such as oil well pipe steel, construction steel, mineral resource mining equipment, etc.
[0139] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high corrosion resistance and high toughness economical steel, characterized in that: The components of the highly corrosion-resistant and highly tough economical steel include, by mass percentage, C: ≤0.03%, Cr: 18.51% to 20.0%, Mo: 1.0% to 3.0%, Ni: 1.0% to 2.8%, Mn: 1.0% to 4%, Si: 0.1% to 0.5%, N: 0.17% to 0.25%, P: ≤0.03%, S: ≤0.01%, and the balance is Fe and unavoidable impurities; Among the components of the highly corrosion-resistant and high-toughness economical steel, 30Ni+17Mn-12Mo-800N≤0; The method for preparing the highly corrosion-resistant and high-toughness economical steel comprises: Step 1: Melting metal raw materials into molten steel; Step 2: smelting the molten steel into continuous casting billets or ingots by continuous casting or mold casting; Step 3: heating and keeping the continuous casting billet or ingot warm, forging and opening the billet to form a forging billet; Step 4: hot rolling the forged billet into a plate through multiple passes; Step 5: subjecting the hot-rolled plate to a solid solution treatment to obtain an economical steel section with high corrosion resistance and high toughness; The microstructure of the highly corrosion-resistant and high-toughness economical steel is a mixed structure of ferrite + austenite + martensite; the volume percentage of austenite is 30% to 50%, and the volume percentage of martensite is 5% to 15%; martensite particles exist in the austenite phase in two forms: one is uniformly dispersed in the austenite grains in the form of fine particles, and the other is distributed in the austenite grains in the form of discontinuous and irregular particles; The elongation of the highly corrosion-resistant and high-toughness economical steel is greater than 45%, and all H2S stress corrosion tests have been passed.
2. The high corrosion resistance and high toughness economical steel according to claim 1 is characterized in that: Among the components of the highly corrosion-resistant and high-toughness economical steel, Cr+3.3Mo+30N-Mn≥26.
3. The high corrosion resistance and high toughness economical steel according to claim 1, characterized in that: Among the components of the highly corrosion-resistant and high-toughness economical steel, 30Ni+17Mn-12Mo-800N≤-80.
4. The high corrosion resistance and high toughness economical steel according to claim 1, characterized in that: The components of the high-corrosion-resistant and high-toughness economical steel include, by mass percentage, C: 0.02%-0.03%, Cr: 18.51%-19.5%, Mo: 1.0%-2.5%, Ni: 1.0%-1.5%, Mn: 1.5%-2.8%, Si: 0.3%-0.5%, N: 0.17%-0.25%, P: ≤0.03%, S: ≤0.01%, and the balance is Fe and unavoidable impurities.
5. The high corrosion resistance and high toughness economical steel according to claim 4, characterized in that: Among the components of the highly corrosion-resistant and high-toughness economical steel, Cr+3.3Mo+30N-Mn≥28.
6. The high corrosion resistance and high toughness economical steel according to claim 1, characterized in that: In the microstructure of the high-corrosion-resistant and high-toughness economical steel, the volume percentage of austenite is 42% to 50%, and the volume percentage of martensite is 6% to 15%.
7. A method for preparing high-corrosion-resistant and high-toughness economical steel, characterized in that: Used to prepare the high corrosion resistance and high toughness economical steel according to any one of claims 1 to 6, comprising: Step 1: Melting metal raw materials into molten steel; Step 2: smelting the molten steel into continuous casting billets or ingots by continuous casting or mold casting; Step 3: heating and keeping the continuous casting billet or ingot warm, forging and opening the billet to form a forging billet; Step 4: hot rolling the forged billet into a plate through multiple passes; Step 5: subject the hot-rolled plate to solid solution treatment to obtain highly corrosion-resistant and high-toughness economical steel.
8. The preparation method according to claim 7, characterized in that: In the step 3, the forging temperature is 1150-1250°C.
9. The preparation method according to claim 7, characterized in that: In the step 5, the temperature of the solution treatment is 1000-1150°C.
Citation Information
Patent Citations
High-plasticity economical duplex stainless steel and manufacturing method thereof
CN102634740A
Heat treatment equipment line for seamless steel pipe, and method for manufacturing high-strength stainless steel pipe
CN104854250A
Economic type duplex stainless steel alloy and preparation process
CN107904521A
High strength stainless steel pipe excellent in corrosion resistance for use in oil well and method for production thereof
CN1836056A
High-strength stainless steel pipe for oil well superior in corrosion resistance to carbon dioxide gas
JP2006016637A